2006
DOI: 10.1038/sj.ijir.3901518
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Peyronie's disease in diabetic patients with erectile dysfunction

Abstract: We attempted in this study to investigate the prevalence of Peyronie's disease (PD) among diabetic patients with erectile dysfunction (ED). Two-hundred and six diabetic patients were further evaluated in this study. Forty-two (20.3%) patients had PD. There were significant associations between PD and risk factors of age, obesity and smoking. All patients with PD had also ED. Penile curvature was present in 82.1% of all patients with PD. Of the patients with PD, 25.4% had pain with or without erection. Signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 15 publications
4
66
2
3
Order By: Relevance
“…The presence of penile plaques and recent penile curvature were similarly reported by diabetic patients with PD in previous studies [38,39]. Diabetes aggravates the pathogenesis of PD.…”
Section: Discussionsupporting
confidence: 65%
“…The presence of penile plaques and recent penile curvature were similarly reported by diabetic patients with PD in previous studies [38,39]. Diabetes aggravates the pathogenesis of PD.…”
Section: Discussionsupporting
confidence: 65%
“…Arafa et al reported a high proportion (20.3%) of 206 diabetic men with ED as also having PD, identifying diabetes as a potential PD risk factor. 11 …”
Section: Prevalence and Significancementioning
confidence: 99%
“…The impact of alcohol use in PD is unclear, with one study supporting an association, 16 and another, larger study failing to show a relationship. 18 Possible associations with diabetes, hypertension, and/or other cardiovascular conditions have been suggested, 11,16 but other studies have failed to corroborate these findings. 17,18 …”
Section: Etiology and Modifiable Risk Factorsmentioning
confidence: 99%
“…Peyronie's disease, which may be associated with sexual dysfunction, is more common in diabetes, with a higher incidence related to a longer duration of diabetes and poor glycaemic control. 37 …”
Section: Diabetes and Other Sexual Dysfunctionsmentioning
confidence: 99%